(untitled) (Web of Teachers: Inderscience Research, 2024)
This study delves into the nuanced expressions of joy and sadness in children aged 6-8 years, exploring the intricate interplay between linguistic acquisition and emotional manifestation. Employing a qualitative descriptive approach, observable verbal and nonverbal cues were analyzed to glean insights into the children’s emotional development. Findings reveal a remarkable command over syntactic structures, enabling them to articulate feelings of joy and sadness effectively. Understanding these expressions provides crucial insights for parents, educators, and caregivers, facilitating tailored support during this pivotal phase of growth.